PENYULUHAN MENCUCI TANGAN DENGAN SABUN SEBAGAI UPAYA PENCEGAHAN COVID-19, DIARE DAN KECACINGAN PADA ANAK-ANAK DI DESA PAROPO KECAMATAN SILAHI SABUNGAN KABUPATEN DAIRI - Linda Hernike Napitupulu; Endang Maryanti, Ani Deswita Chaniago, Mariana, Putri Afni Nasution, Iqwara Samanta Putri (Adiba Aisha Amira, 2022)
School-age children are a group of people who are expected to grow into potential human resources in the future so they need to be considered and prepared to be able to grow perfectly both physically and intellectually. Washing hands with running water is one way to prevent COVID-19, diarrhea and worms. At school age children are very susceptible to contracting the disease. The purpose of this activity is to increase children's knowledge about efforts to prevent the disease. The results of community service showed that there was an increase in knowledge about washing hands with soap in participants. It is hoped that this activity can be carried out regularly so that children as the next generation become healthier, this can increase their enthusiasm for learning.